AB0932 FACTORS IN ACHIEVING TARGET SERUM URIC ACID LEVELS IN OUTPATIENT GOUT MANAGEMENT IN A MALAYSIAN TERTIARY RHEUMATOLOGY CENTRE. (2nd June 2020) - Mustapha, M. H.; Baharuddin, H.; Zainudin, N.; Ch'ng, S. S.; Mohd Yusoof, H.; Lau, I. S.; Mohd Zain, M.; Rosman, A.
Abstract : Background: Gout is one of the most common inflammatory arthropathies. A target serum uric acid of less than 300µmol/l is recommended when tophi are present, and less than 360µmol/l for non-tophaceous gout. Urate-lowering therapy (ULT) should be titrated until the target is achieved and long-term maintenance of the target concentration is recommended. Although ULT has been proven to reduce the uric acid level, less than half of treated patients achieved the target serum uric acid (sUA) in real-world clinical practice. Objectives: To assess the mean treat-to-target achievement in outpatient management of gout by the tertiary rheumatology centre and to identify factors influencing the success rate. Methods: Retrospective cross-sectional study of all patients with gout attending out-patient clinics in a rheumatology referral centre from 1 st January 2018 until 31 st December 2018. Electronic medical records were reviewed. The successful target achievement is defined as mean of all available sUA in 2018 which is ≤360 and ≤300µmol/l for non-tophaceous and tophaceous gout respectively. Chronic kidney disease (CKD) is defined as glomerular filtration rate of less than 60ml/min. Results: There were 251 patients analysed with mean age of 56.3±13.8 years and disease duration of 10.5±9.2 years. Majority were males (215, 85.7%) and 133 (53%) patients had tophaceous gout. The rate of success achieving the target SUA level of ≤360 and ≤300µmol/l were 33.9% (40) and 15.8% (21) in non-tophaceous and tophaceous gout respectively. However, in patients who are compliant, the target sUA achieved is 52.4% (33) and 31.7% (19) in non-tophaceous and tophaceous gout respectively. Characteristics of patients who achieved the targeted sUA were patients of more than 50 years old (48, 78.7%), without family history of gout (29, 65.9%), were prescribed colchicine prophylaxis upon initiating ULT (46, 76.7%), with absence of joint erosions (34, 73.9%) and those with normal creatinine clearance (40, 65.5%). There were 120 (48.4%) patients who were compliant to ULT. In 42 compliant patients who achieved target sUA, the mean allopurinol dose is 289.66mg±101.2 and 369.23mg±175 in non-tophaceous and tophaceous gout respectively. Sub-analysis in 31 compliant CKD patients, revealed no difference in allopurinol dose between those who achieved versus non-achieved target sUA (mean 243mg versus 263mg respectively). However, we noted that 11 (61%) CKD patients with tophi did not achieved target sUA at dose less than 300mg allopurinol. Lower achievement of target sUA was significantly associated with presence of tophi (p=0.001), poor compliance (p= 0.000) and presence of more than one comorbidity (p=0.041). Conclusion: There are several challenges in achieving target uric acid level contributed by both patient and clinician factors such as compliance, presence of comorbidity and ULT dose. Our study suggests that higher dosage of allopurinol is required in patients with tophaceous gout, with or without renal impairment. However, the limitation of this study is, the small number of subjects which therefore needs further investigation. References: [1]Roddy, E., Packham, J., Obrenovic, K., Rivett, A., & Ledingham, J. M. (2018). Management of gout by UK rheumatologists: a British Society for Rheumatology national audit. Rheumatology, 57(5), 826–830. [2]Katayama A, Yokokawa H, Fukuda H, et al. Achievement of Target Serum Uric Acid Levels and Factors Associated with Therapeutic Failure among Japanese Men Treated for Hyperuricemia/Gout. Intern Med. 2019;58(9):1225–1231. Disclosure of Interests: Mariam Hamid Mustapha: None declared, Hazlyna Baharuddin Speakers bureau: Sanofi, J&J, Norliza Zainudin: None declared, Shereen Suyin Ch'ng Speakers bureau: Novartis, Pfizer, GSK, Habibah Mohd Yusoof: None declared, Ing Soo Lau: None declared, Mollyza Mohd Zain: None declared, Azmillah Rosman: None declared